Metode kerja pengujian bending hasil pengelasan pipa dengan metode SMAW elektroda E7018 standar ASTM D790 - Khristyson, Samuel Febriary; Cahyo, Indro Dwi (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
Bending testing is one way of testing welding results or materials which are included in destructive testing. Selection of decisions in determining the choice of the sequence of process methods can indicate the level of accuracy and effectiveness of an activity. The purpose of this study was to find out the criteria for work methods for testing the results of welding on pipes with a hydraulic press in the Welding and Ship Construction Education and Research Laboratory, Industrial Technology Department, Vocational School, Diponegoro University, Semarang. An alternative method with a rational approach to find out the criteria for each function of the testing process is presented in this study. The highest alternative value, 80%, is in the first preference where the second alternative method is used as a reference with 2 practitioners and an average usage time of 75 minutes. So that the selection of function parameters as seen from the aspects of function, economy, and time used can be adjusted to the usefulness of the work equipment in the laboratory.